A randomized controlled trial to evaluate the feasibility of the Wii Fit for improving walking in older adults with lower limb amputation. (January 2017) - Imam, Bita; Miller, William C; Finlayson, Heather; Eng, Janice J; Jarus, Tal
Objective: To assess the feasibility of Wii.n.Walk for improving walking capacity in older adults with lower limb amputation. Design: A parallel, evaluator-blind randomized controlled feasibility trial. Setting: Community-living. Participants: Individuals who were ⩾50 years old with a unilateral lower limb amputation. Intervention: Wii.n.Walk consisted of Wii Fit training, 3x/week (40 minute sessions), for 4 weeks. Training started in the clinic in groups of 3 and graduated to unsupervised home training. Control group were trained using cognitive games. Main Measures: Feasibility indicators : trial process (recruitment, retention, participants' perceived benefit from the Wii.n.Walk intervention measured by exit questionnaire), resources (adherence), management (participant processing, blinding), and treatment (adverse event, and Cohen's d effect size and variance). Primary clinical outcome : walking capacity measured using the 2 Minute Walk Test at baseline, end of treatment, and 3-week retention. Results: Of 28 randomized participants, 24 completed the trial (12/arm). Median (range) age was 62.0 (50-78) years. Mean (SD) score for perceived benefit from the Wii.n.Walk intervention was 38.9/45 (6.8). Adherence was 83.4%. The effect sizes for the 2 Minute Walk Test were 0.5 (end of treatment) and 0.6 (3-week retention) based on intention to treat with imputed data; and 0.9 (end of treatment) and 1.2 (3-week retention) based on per protocol analysis. The required sample size for a future larger RCT was deemed to be 72 (36 per arm). Conclusions: The results suggested the feasibility of the Wii.n.Walk with a medium effect size for improving walking capacity. Future larger randomized controlled trials investigating efficacy are warranted.